STUDENTS’ ENGAGEMENT WITH SOCIAL MEDIA REELS: SCOPE FOR NEWS OUTLETS - Kannan, S.; Anuradha, M. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Youth in a country like India have undergone drastic lifestyle changes as a result of social media. Their engagement goes beyond just viewing or creating content. Since 230.25 million people use short videos, India is the biggest market for Instagram reels. Even after social activists, parents, and researchers point out a number of drawbacks, 54% of young people in India do not want to stop using social media, according to Pew Research (2012). The engagement ratio has also gone up to 800 likes on average (Daniel Ruby, 2022). In January 2022, India had 17.8% of its population using Instagram, among which the most frequent users were aged between 18 and 24. The use of social media reels among the Gen Z category has gone up. Hence, the present study tries to address the following objectives using a mixed-methods approach: a survey using a structured online questionnaire and a focus group discussion among students. The findings of the study would help media outlets market their news content to a wider audience on one side and develop the habit of consuming news among the Gen Z audience.